The Effect of Self-Management Application on Academic Procrastination in Nursing Students at STIKep PPNI West Java - Suryani, Ade Irma; Sudrajat, Diwa Agus Sudrajat; Ibrahim, Masdum; Kumala, Tria Firza (STIKep PPNI Jawa Barat, 2024)
Aims: To determine the effect of self-management applications on academic procrastination in nursing students at STIKep PPNI West Java. Methods: This study used a quantitative quasi-experimental method with a two-group pretest-posttest design. The number of respondents was 60 with sampling using a proportionate stratified random sampling technique consisting of 30 intervention groups and 30 control groups, with inclusion criteria for undergraduate nursing students. The instrument used was the Tuckman Procrastination Scale. Univariate analysis used mean, SD, min, max and bivariate analysis using paired sample t test and independent sample t test. Results: Based on the results of the paired sample t-test, the p-value is 0.000 (p <0.05) and the independent sample t-test has a p-value of 0.000 (p <0.05), which means that there is a significant differences in value between the intervention groups and the control group so that Ha is accepted and H0 is rejected. Conclusions: The study found a significant reduction in academic procrastination in the intervention group compared to the control group, due to structured self-management. The intervention group experienced better behavioral changes, while the control group experienced a decrease. The study also found significant differences in self-management implementation through four stages: self-monitoring, self-contracting, stimulus control, and self-reinforcement.